Very late diagnosis of pituitary stalk interruption syndrome in a patient with dengue with warning signs - Sernaque Mechato, Roger Antonio (2024)
Pituitary stalk interruption syndrome (PSIS) is a congenital genetic disorder that causes hypopituitarism, which is characterized by hypoplasia of the adenohypophysis, ectopic neurohypophysis and pituitary stalk interruption. The clinical manifestations are related to varying degrees of pituitary hormone deficiency (panhypopituitarism). The diagnosis is usually made late or goes unnoticed because it depends on the clinical manifestations presented, a fact that is associated with high morbidity and mortality in patients. We present the case of a 19-year-old female patient with a pathological history of nystagmus, toxoplasmosis, stunted growth and delayed pubertal development. She was admitted to the hospital emergency room because she presented with fever, dyspnea, polyarthralgia, headache, vomiting and oral intolerance. During hospitalization, sustained hypoglycemia refractory to the administration of dextrose was evidenced. Hence, laboratory tests were performed, revealing varying degrees of pituitary hormone deficiencies, with notable deficits in growth hormone, thyroid hormone and gonadotropic hormones, as well as hypocortisolism due to a deficiency in adrenocorticotropic hormone. Consequently, she was diagnosed with dengue with warning signs and panhypopituitarism. She responded well to the established treatment, showed good progress and was discharged with hormone replacement therapy. Early and timely diagnosis of PSIS prevents issues related mainly to metabolism, growth and development. Therefore, an adequate hormonal profile and imaging study of the pituitary gland is the key to diagnosis and treatment. In addition, timely recognition and treatment improve the prognosis, quality of life and life expectancy of patients.